Fortalecendo o protagonismo feminino na área da computação no ensino básico: relato de experiência de duas Escolas da Rede Pública em Santarém – Pará - Brasil - CASTRO, Alessandra Alves de (Universidade Federal do Oeste do Pará, 2024)
Digital technologies are increasingly present in non-formal learning environments, referring to spaces where teaching does not occur systematically and, therefore, possibilities of introducing technological resources in the school environment may arise. The courses in the computational area have proved significant for the male audience, since the female presence in computing is still a minority. In this context, it is important to carry out actions aimed at teaching computing to students to arouse their interest in computing. The present research aimed to plan workshops on computational thinking and programming language in basic education in order to stimulate the female audience in the area of computing. The trainings were developed in two high schools for public school students in the city of Santarém-Pará-Brazil. The methodology with a qualitative approach was divided into presentation of the proposal in the schools of interest, selection of students, realization of the workshops, evaluation of the workshops and finally the analysis. At the end of the actions, an electronic questionnaire was made available in order to analyze the contribution of the training developed. The results showed that the students felt motivated to enter a course in the computational area after the execution of the trainings since they did not have previous knowledge related to computational contents, consequently there was no perspective of interest in this theme.